Review of current understanding of post‐traumatic osteoarthritis resulting from sports injuries. Issue 3 (22nd July 2016) - Carbone, Andrew; Rodeo, Scott
ABSTRACT: Certain types of joint injuries, common in athletes, are known to have a high association with the development of osteoarthritis (OA). Post‐traumatic osteoarthritis (PTOA) is especially debilitating due to its earlier onset than traditional OA, and its predisposition to affect a younger and more active population. Five common athletic injuries have been demonstrated to be risk factors for the development of OA. These include ACL rupture, meniscus tear, glenohumeral instability, patellar dislocation, and ankle instability. Though the mechanisms responsible for the development of PTOA are not entirely clear, certain kinematic, biologic, and mechanical factors have been implicated. In addition, there has been an increased emphasis on development of new methods to detect early OA changes in patients with known risk factors, as early intervention may prevent the development of end‐stage OA. New imaging modalities as well as the identification of specific biomarkers may allow earlier detection. Though these developments hold promise, it is not entirely known what steps we can take today to prevent the future development of OA, even with early detection. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:397–405, 2017.